Acceptance of Family Planning Practices Among Reproductive Age Women in a Rural Area of Etawah - Kiran Krishnappa; Amit Kaushik; Pankaj Kumar Jain; Sandip Kumar; Nandini Gupta; Mahima Chandini (Medsci Publications, 2020)
Introduction: Despite considering family planning as a priority in population policy, our country is still long way to achieve a stable population, especially in rural area. This study was schemed to evaluate the awareness and the prevalence of contraceptive use in a rural area of Etawah. Material & Methods: A house to house survey was conducted in 5 villages in Saifai block of Etawah. A sample of 810 married woman of reproductive age group were interviewed to obtain information on sociodemographic profile and family planning. Results: The average age of study respondents was 29.19 ± 6.7 years. Majority (44.7%) of respondents belonged to 26-35years and 40% were illiterate. Only 76.6% of the respondents were aware of at least one method of family planning. Nearly 50% were aware of Female sterilization, Condoms and IUCD. Univariate analysis revealed age, education, caste and partner's education were significant factor affecting awareness of family planning. Contraceptive usage was associated with age, family size and decision making ability. Multivariate awareness revealed that education significantly affected awareness and partner's education was significantly associated with contraceptive usage. Conclusion: Study showed that there is a significant gap between awareness and use of contraception. Age, education, family size and partner's education were significant factors affecting acceptance of family planning in this rural setup.